Physico-mathematical model for determining the direction in space to point sources of gamma radiation using spherical absorber - Grigoryev, A. N.; Bilyk, Z. V.; Pettersson, I.; Litvinov, Yu. V.; Polyansky, N. E.; Sakun, A. V.; Marushchenko, V. V.; Cherniavskyi, I. Yu.; Voronkin, E. F.; Sosnutska, O. O.; Petrukhin, S. Yu.; Indykov, S. N.; et al. (STC "Institute for Single Crystals", 2018)
Physico-mathematical model for determining the direction in space to point sources of gamma radiation using a spherical absorber was developed. CdTe detectors of appropriate sizes are placed in the regular pyramid tops under absorber. The physico-mathematical model allowed, taking into account the exponential attenuation of gamma radiation by the absorber, to find the distance from the location of any CdTe sensor to the surface of sphere in any direction in space. Calculated information and signal received from the detectors, correlate to each other. The ratios found depend on the angle to the source of gamma radiation and represent the ratio of transmittance coefficients for four sensors. A methodology for locating the developed device in space, which allowed to obtain dependence of the calculated ratios from the angle in space for θ = 90° and φ from 0 to 360° in increments of 15° was proposed. Each direction in space corresponds to a set of six respective ratios.

Розроблено фізико-математичну модель визначення напрямку на точкові джерела гамма-випромінювання у просторі з використанням кульового поглинача. Детектори з CdTe необхідного розміру розміщують у вершинах правильної піраміди під поглиначем. Фізико-математична модель дозволила з зрахуванням експоненційного ослаблення гамма-випромінювання поглиначем знаходити відстань від розташування будь-якого CdTe датчика до поверхні кулі у будь-якому напрямі у просторі. Розраховану інформацію-сигнал, що отримано від детекторів, співвідносять один до одного. Знайдені співвідношення залежать від кута на джерело гамма-випромінювання та являють собою відношення коефіцієнтів пропускання для чотирьох датчиків. Запропоновано методику розташування розробленого засобу у просторі, що дозволила отримати залежність розрахованих співвідношень від кута в просторі для θ = 90° та φ від 0° до 360° з кроком 15°. Кожному напрямку у просторі відповідає набір з шістьох відповідних співвідношень.
Фізико-математична модель визначення напрямку у просторі на точкові джерела гамма-випромінювання з використанням кульового поглинача
Keywords: physico-mathematical model; determining the direction; detector under absorber; source of gamma radiation; spherical absorber